A Real-Business-Cycle model with energy use: Lessons for Bulgaria (1999-2018) - Aleksandar Vasilev (Journal of Mathematical Economics and Finance, 2023)
We introduce energy as a productive input into a real-business-cycle model with government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). We investigate the quantitative importance of the presence of energy, and the potential relevance of energy price shocks as driving forces behind the observed business cycle fluctuations in Bulgaria. In particular, a positive shock to energy prices in the model works like a negative technological shock. Allowing for the presence of energy as a factor of production does not substantially improves the model performance against data, and is thus an unlikely driver of business cycle fluctuations in Bulgaria.
Keywords: E32; 330; Business fluctuations; energy use